Psychological stress in sports coaches: A review of concepts, research, and practice - Fletcher, D.; Scott, M. (Journal of Sports Sciences, 2010)
Sports coaches operate within a complex, ever-changing environment that imposes many pressures on them. Here, we address the psychological impact of these demands via a critical review of the literature pertaining to stress in sport coaches. The narrative is divided into three main sections: (1) conceptual and definitional issues, (2) theoretical and empirical issues, and (3) implications for applied practice. The review focuses on the environmental stressors that coaches encounter, their appraisals of and responses to these demands, and the impact this has on their personal well-being and job performance. The influence of various personal and situational characteristics is also discussed. A key message to emerge from this review is that the potential health and performance costs of psychological stress to sports coaches are significant. The rapid rate of change in contemporary sport and the dynamic nature of stress mean that stress in coaches is an ongoing problem that needs to be monitored and addressed.